(NmATEMATI^ESKOE MODELIROWANIE TE^ENIJ STRATIFICIROWANNOJ VIDKOSTI (B/s - (NbELOLIPECKIJ(B, (NwIKTOR mIHAJLOWI^s; (NkOST@K(B, (NwLADIMIR `RXEWI^s; (N{OKIN(B, (N`RIJ iWANOWI^s; (NkOWENQ(B, (Nw(B.(Nm(B.s ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 160-169 (176 (NNAZW(B.), 174 (15 (NNAZW(B.)s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NkRASNOQR(B. (NNAU^(B. (NCENTR(B, (Nwcs
Keywords: (NvIDKOSTI STRATIFICIROWANNYEs